The Effect of Role Conflict, Role Ambiguity and Ethical Sensitivity on Auditor Performance with Intellectual Intelligence as a Moderating Variable - Sangkala, Masnawaty; Hasan, Muhammad; Rum, Muh. (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to analyze the effect of role conflict, role ambiguity, and ethical sensitivity on auditor performance and intellectual intelligence as a moderating variable on the relationship between these factors and auditor performance. Data were collected from 200 respondents who were auditors at the Makassar City BPKP Office using a questionnaire. The data analysis technique used is multiple regression with a moderated regression analysis (MRA) approach. The results showed that role conflict and role ambiguity have a significant negative effect on auditor performance, while ethical sensitivity has a significant positive effect on their performance. In addition, intellectual intelligence moderates the relationship between role conflict and auditor performance so that the higher the intellectual intelligence of an auditor, the negative impact of role conflict on his performance will be reduced. However, intellectual intelligence does not moderate the relationship between role ambiguity and performance.